THE ROLE OF RELIGION IN THE PROCESS OF RECONCILIATIONIN BOSNIA AND HERZEGOVINA: AN EMPIRICAL RESEARCH (Религиски дијалог и соработка, 2021)
The paper will show the results of a research on the roleof religion in the reconciliation process that took place on theterritory of Bosnia and Herzegovina from 2012 to 2019. The firstpart of the paper will show the views of the general populationfrom 2606 respondent. The second part will show a qualitativeanalysis of the content of the interview with the representatives ofthree traditional religious communities in Bosnia and Herzegovina.The interview was conducted from the summer of 2018 until spring2019, with people who are prominent in their public role in societywith professors of religious universities, religious school directorsand religious teachers who were part of this sample, patronsof Orthodox, Islamic, Roman Catholic, Judaism and Protestanttheologians. The results of the survey show that there arepotentials for building a stable process of reconciliation. Primarily,the right to choose is for the common good of all citizens of Bosniaand Herzegovina in order to create an atmosphere of acceptance,understanding and respecting differences of members of differentnational backgrounds and religious traditions. There are manyways to realize the process of reconciliation, and those that arerecognized are open dialogue about the past, admitting andapologizing, recognizing the victims and respecting their religiousidentity, giving special attention to minority groups that feelvulnerable in certain areas. Religion has potentials for reconciliationif their believers accept both the differences and the commonalitiesof others. Religious leaders, more than lay people, are in a positionto contribute to reconciliation.